การศึกษาเปรียบเทียบการสืบสวนสอบสวนตามกฎหมายวิธีพิจารณาความอาญา ของประเทศไทยกับประเทศมาเลเซีย - วิเศษสินธุ์ ฉัตตมาศ (Al-HIKMAH Journal, 2018)
This research aims to study the Criminal Procedure Code on the investigation and inquiry of Thailandin order for comparison and contrast between the Criminal Procedure Code of Thailand and Malaysia as well as the intendment of legal provision and law enforcement of both countries. As the formal establishment of the ASEAN Economic Community does not only affect the economic aspect but also creates the trade, investment and labor liberalization facilitating the communication among AEC people. Despite the Community is compared to the establishment of new and bigger society, each country has its own law which governs the offenses. Accordingly, this research has 2 objectives as follows. Firstly, this is to study and research the investigation and inquiry with the intention of offering benefits to people required to involve in the criminal procedure and the investigation and inquiry of Malaysia so that they understand the different context of legal provision, intendment of law or law enforcement. Secondly, this is to understand the problems, differences and regulations of enforcement of the Criminal Procedure Code of Thailand and Malaysia on the investigation and inquiry and to analyze whether Thailand’s current Criminal Procedure Code should be amended and accords with the international regulations. According to the study, it found that the intendment of the Criminal Procedure Code on the investigation and inquiry of Thailand and Malaysia shared similarity and accordance fully. For example, the international regulations were adopted to enact their domestic legal provisions but had different details. For instance, Malaysia could enforce the criminal procedure with other laws in addition to the Criminal Procedure Code by clear legal provisions in order to enforce the criminal procedure immediately. Furthermore, the Malay authorities were responsible for providing lawyers unconditionally but there was no female official to inquire female victims in sexual cases. On the issue that Malaysia protecting right more than Thailand, it found that Malaysia would authorize a person or group of persons to protect child’s right in the criminal case. Moreover, according to the study, it found the discordance with the international regulations in both countries, one case in each country. Regarding to Thai laws, the authorities would provide a lawyer without costs and expenses for specific cases with death penalty or under 18-year alleged offender on the date the inquiry official notifies the allegation or case with prison sentence which the alleged offender required the lawyer only. With regard to Malaysia laws, there were no strict provisions for procedures, conditions and limitations to collect scientific evidences